2015
DOI: 10.1108/gm-12-2013-0135
|View full text |Cite
|
Sign up to set email alerts
|

The impact of gender perceptions and professional values on women’s careers in nursing

Abstract: Purpose -Within nursing, there appears to be two enduring sets of assumptions: firstly, that woman with children should prioritise the care of children; and secondly, that nursing standards require nurses to put their profession above other priorities. Commitment is linked to full-time working which contrasts sharply with the reality for many women with children who need to work part-time and are not able to change or extend working hours. Design/methodology/approach -This qualitative research involved the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 13 publications
2
30
1
1
Order By: Relevance
“…Organisations have an important function to raise awareness of, and educate people on, genderbased expectations and perceptions around merit, since Kumra (2017) found that these perceptions could disfavour women in advancing to senior roles, in line with McIntosh et al (2015) and this study's findings.…”
Section: Implications For Organisationssupporting
confidence: 74%
See 1 more Smart Citation
“…Organisations have an important function to raise awareness of, and educate people on, genderbased expectations and perceptions around merit, since Kumra (2017) found that these perceptions could disfavour women in advancing to senior roles, in line with McIntosh et al (2015) and this study's findings.…”
Section: Implications For Organisationssupporting
confidence: 74%
“…The authors intended to explore the perceptions of sponsors in particular and therefore had to include top management in their sample. Scholars like McIntosh, McQuaid and Munro (2015) highlight that gender perceptions, by both males and females, can be biased against women, and these produce gender inequalities in employment. For this reason, focussed attention is required to develop women's talent in organisational settings, through leadership training or team-building programmes, which encourage self-reflection of both men and women around gender-based assumptions and expectations, as Ely, Ibarra and Kolb (2011) recommend.…”
Section: Talent Management Interventionsmentioning
confidence: 99%
“…Using Bourdieu's (1984) habitus concept, what happens may be considered a change in the habitus, which includes a personal development not only focused on the future occupation, and yet, this development is expected to become an asset in working with people in need of care. There is also a connection to research that highlights that personal, feminine-coded traits are considered a central part of the vocational knowledge for health care givers (Lindgren, 1992;Wreder, 2005;Huppatz, 2012;McDonald, 2013;McIntosh, McQuaid & Munro, 2014;Rehn & Eliasson, 2015). However, in this citation there is also a significant difference when the informant talks about courage and strength, traits that are seldom a part of a feminine caring disposition.…”
Section: Creating Motivation and Interestmentioning
confidence: 96%
“…Despite the proliferation of work-life balance policies, the stereotypical career leading to higher level positions is still largely considered to be a full-time occupation that is pursued on a continuous basis often involving extra hours and a high level of dedication (McIntosh et al, 2012(McIntosh et al, , 2015. Hakim (2006) argues that not all occupations can be domesticated with some involving considerable travel for long periods (e.g., new reporting, investment banking, airline industry) and others requiring long or irregular hours.…”
Section: Work-life Balancementioning
confidence: 99%